The Design of an Energy Harvesting Wireless Sensor Node for Tracking Pink Iguanas - Pierpaolo Loreti; Alexandro Catini; Massimiliano De Luca; Lorenzo Bracciale; Gabriele Gentile; Corrado Di Natale (Sensors, 2019)
The design of wireless sensor nodes for animal tracking is a multidisciplinary activity that presents several research challenges both from a technical and a biological point of view. A monitoring device has to be designed accounting for all system requirements including the specific characteristics of animals and environment. In this work we present some aspects of the design of a wireless sensor node to track and monitor the pink iguana of the Galápagos: a recently discovered species living in remote locations at the Galápagos Islands. The few individuals of this species live in a relatively small area that lacks of any available communication infrastructure. We present and discuss the energy harvesting architecture and the related energy management logic. We also discuss the impact of packaging on the sensor performance and the consequences of the limited available energy on the GPS tracking.